Effect of Soil Polluted with Crude Oil on Some Wood Properties of Casuarina equisetifolia - Ali, B. A. Abd; Ali, H. H. (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2016)
The current experiment was conducted to explore the effect of soil crude oil ( crude oil ) pollution on some wood properties of   Casuarina equisetifolia.      Four levels of pollution were applied on 40 (one-year) old seedlings . Measurements were taken by cutting the trees after two growth seasons from date of pollution .The studied Properties were fiber length, diameter, wall thickness, and specific gravity of external and internal wood.  Results showed an adverse effect of pollution on fiber diameter more than on fiber length. While wall thickness did not affect.  Fiber dimensions of external wood showed higher values  than that of internal one, especially for fiber length. Specific gravity was affected by pollution and its interaction. A significant increase in specific gravity was observed with higher pollution levels for external wood only i.e. for the two layers formed after pollution.